SOCIAL AND PHILOSOPHICAL ANALYSIS OF SPIRITUAL CHANGES IN SOCIETY - Togayev Shavkat Hurramovich (Bright Mind Publishing, 2025)
In this work, the analysis of the complex processes taking place in the modern globalized world cannot be carried out without taking into account socio-philosophical factors. In the new Uzbekistan, life in the spirit of activity and creativity becomes a necessity of life, a social necessity for everyone. The article also provides a philosophical analysis of the principles of social justice in New Uzbekistan, as well as changes in the spiritual and social spheres of society, their features.
Keywords: Constitution, New Uzbekistan, social justice, law, democratic state, freedom, justice, civil society, rule of law, development, human rights, social policy.